Study of the DNA damage and cell death in human peripheral blood mononuclear and HepG2/C3A cells exposed to the synthetic 3-(3-hydroxyphenyl)-7-hydroxycoumarin - Pereira, André Rogerio [UNESP]; Campos, Ashley Silva [UNESP]; Matos, Maria João; Maistro, Edson Luis [UNESP] (Taylor & Francis, 2024)
Hydroxycoumarins are an important source of biologically active compounds. Previous studies have shown that the number and position of the hydroxyl substituents in the scaffold play an important role for the observed biological activity. In the present study, 3-(3-hydroxyphenyl)-7-hydroxycoumarin was synthesized, and potential cytogenotoxic effects determined in human HepG2/C3A cells displaying phase 1 and phase 2 enzymes (metabolizing cell ability) and compared to human peripheral blood mononuclear cells (PBMC) without xenobiotics metabolizing capacity. Cell viability was determined with concentrations between 0.01 and 10 µg/ml of 3-(3-hydroxyphenyl)-7-hydroxycoumarin using MTT (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide) and trypan blue tests. Genotoxicity was determined utilizing the comet assay, and the clastogenic/aneugenic potential employing the micronucleus (MN) test. The results of the in vitro cytotoxicity assays showed a significant decrease in cell viability of PBMC following exposure to 10 µg/ml concentration of the studied compound after 48 and 72 hr. Comet assay observations noted significant DNA damage in PBMC after 4 hr treatment. No marked cytogenotoxic effects were found in HepG2/C3A cells. No chromosomal mutations were observed in both cell lines. It is important to note that 3-(3-hydroxyphenyl)-7-hydroxycoumarin may exert beneficial pharmacological actions at the low micromolar range and with half-life less than 24 hr. Therefore, the results obtained encourage the continuation of studies on this new molecule for medicinal purposes, but its potential toxicity at higher concentrations and longer exposure times needs to be investigated in further studies.
Keywords: cell viability; comet assay; HepG2/C3A cells; human leukocytes; micronucleus test; risk assessment